Necessary Management Rules to Build a Company with Fully Equipped Techniques - G. ., SuryanagaRaju; R., Puviarasi (International Journal of Psychosocial Rehabilitation, 2020)
The fourteen principles that were discovered by Henri Fayol and their applications have been implemented in start-up businesses and their implications analyzed. Relating to this publishing work, an extensive review has been done. This has produced better understanding, modifications, and concepts of principles. For suitability of start-up businesses, the benefits, importance, strengths, as well as weaknesses of these were tested. For studying in a directional perspective, in Lagos, Nigeria, from start-up data was studied. Based on the literature results that have been obtained from the data, Fayol’s principles of control are applicable to start-up businesses, which are existing in organizations.